ZnSe/CdSe core–shell nanoribbon arrays for photocatalytic applications. Issue 5 (8th January 2020) - Sun, Chengcheng; Li, Tingting; Wen, Weijia; Luo, Xiangdong; Zhao, Lijuan
Abstract : Core–shell structures can improve the properties of materials due to their special structure and have attracted considerable attention for their applications in many fields. Abstract : Core–shell structures can improve the properties of materials due to their special structure and have attracted considerable attention for their applications in many fields. In this work, uniformly distributed ZnSe nanoribbon arrays (NRAs) on zinc foil were prepared. ZnSe/CdSe core–shell NRAs were obtained through a cation replacement process and the ribbon morphology was preserved well. ZnSe/CdSe core–shell NRAs exhibited an enhanced photocatalytic performance in the degradation of certain dyes compared with pure ZnSe NRAs, which was due to the broader light absorption range and lower carrier recombination rate in the core–shell NRAs. ZnSe/CdSe core–shell NRAs also showed improved photoelectrochemical (PEC) performance, which proved the lower carrier recombination rate to some extent. The strategy provides a flexible and straightforward route for design and preparation of inverted core–shell NRAs. The in situ growth of ZnSe/CdSe core–shell NRAs on a Zn substrate allows easy recycling in photocatalytic application, avoiding secondary contamination, which is promising for new opportunities in energy and environment applications.